Climate engineering: early reflections on a complex conversation - Moore, N.; Benmazhar, H.; Brent, K.; Du, H.; Iese, V.; Koné, S.; Luwesi, Cush Ngonzo; Scott, V.; Smith, J.; Talberg, A.; Thompson, M.; Zhuo, Z. (Brill, 2015)
This is a background account and formal statement prepared by participants in the Institute for Advanced Sustainability Studies’ Climate Engineering Summer Course, held between 2 and 17 August 2014 in Potsdam, Germany.